Histological Development of Selected Neural Structures of Dark-Sided Chorus Frog, Microhyla heymonsi (Amphibia: Anura) - Tang May Yin, Joan; Hasan Adli, Durriyyah Sharifah (Malaysian Journal of Science, 2010)
The development of selected neural structures of Dark-sided Chorus Frog, Microhyla heymonsi, from tadpole to adult was characterized from the histological aspect. Six developmental stages studied were the early tadpole, pre-metamorphosis, pro-metamorphosis, metamorphic climax, froglet and the adult. For M. heymonsi, metamorphosis is part of a normal developmental process, during which it undergoes transition from an aquatic tadpole into a terrestrial frog. The four neural structures focused on were: (a) cerebral hemispheres of the forebrain, (b) optic lobe of the midbrain, (c) medulla oblongata of the hindbrain, and (d) spinal cord. The specimens were processed for visualization according to H&E histological staining technique. The observed histological changes and the increase in size of each neural structure were in turn correlated to the external morphology and behaviour of different stages of the developing M. heymonsi. Changes in the cellular distribution, especially in the area surrounding the ventricle and other specific changes of the selected neural structures are reported. Apart from that, results also showed changes in the ventricular shape and/or size of each structure. All the apparent changes detected, possibly, represented the maturation of the neural structures in correlation to the metamorphosis process. Results from the light microscopy observations are presented in the form of photomicrographs and sketches with highlights of changes of the selected neural structures.